Lessons for the UK on implementation and evaluation of breastfeeding support: evidence syntheses and stakeholder engagement - Anna Gavine; Albert Farre; Fiona Lynn; Shona Shinwell; Phyllis Buchanan; Joyce Marshall; Sara Cumming; Louise Wallace; Angie Wade; Elayne Ahern; Laura Hay; Marianne Cranwell; et al. (NIHR Journals Library, 2024)
Background Breastfeeding impacts positively on multiple health outcomes, but < 50% of UK women breastfeed at 8 weeks. Women with long-term conditions face additional challenges in breastfeeding. Objectives To synthesise global and UK evidence to co-create an implementation and evaluation toolkit for cost-effective breastfeeding support in the NHS. Design Evidence syntheses with stakeholder engagement. Review methods Systematic reviews examined effectiveness of breastfeeding support for (1) healthy women and (2) women with long-term conditions using Cochrane Pregnancy and Childbirth Group methods. Mixed-methods systematic reviews synthesised process evaluations of effective breastfeeding support interventions for healthy women and experiences of receiving/providing support for breastfeeding women with long-term conditions. Cross-study synthesis integrated qualitative and quantitative findings. Systematic reviews synthesised evidence on the incremental costs and cost-effectiveness of breastfeeding support following National Institute for Health and Care Excellence guidance. All searches were conducted from May 2021 to October 2022. Stakeholder engagement and toolkit development comprised online discussions, a modified Delphi study, focus groups and four workshops. Participants were 23 stakeholders, 16 parents in the parents' panels, 15 women in the focus groups and 87 stakeholders who attended the workshops. Results We found considerably more interventions designed for healthy women (review 1) than aimed at women with long-term conditions (reviews 1 and 4); approximately half of the studies were targeted at groups at higher risk of poor breastfeeding outcomes, and the impact of support may be different in these populations. Despite this, studies from review 2 found that women perceived the provision of support as positive, important and needed. Studies from review 5 echoed a range of suggestions from participants regarding potential strategies to improve breastfeeding support, with the most widely reported being the need to acknowledge the role and influence of other sources of support (e.g. partners, family, friends, peers, external professionals, web-based resources) and involving these sources in the provision of breastfeeding support for women with long-term conditions. In reviews 3 and 6, there was uncertainty about the cost-effectiveness of breastfeeding support interventions due to the limited number of studies and lack of good-quality evidence. Limitations There was a lack of evidence for the effectiveness and cost-effectiveness of breastfeeding interventions in the UK. There was often insufficient information reported about intervention characteristics. Conclusions 'Breastfeeding only' support probably reduces the number of women stopping any or exclusive breastfeeding. The evidence for 'breastfeeding plus' interventions is less consistent, but these may reduce the number of women stopping exclusive breastfeeding at 4-6 weeks and at 6 months. We found no evidence of differential intervention effects regarding mode of provision or provider. Cost-effectiveness is uncertain due to the lack of good-quality evidence. Key enablers of successful implementation were responsiveness and tailoring of interventions to both women's and supporters' needs. Breastfeeding support as delivered in the included studies probably has little to no effect on breastfeeding outcomes for women with long-term conditions. The mixed-methods synthesis and stakeholder work identified that existing interventions may not address the complex needs of these women. The main study output is a co-produced toolkit to guide implementation and evaluation of breastfeeding support services in the UK. Future work Evaluation of breastfeeding support for all women, particularly those at risk of poor breastfeeding outcomes (e.g. long-term conditions, deprivation). This could involve tailoring the toolkit to local contexts via implementation and effectiveness studies or using quality improvement studies. Study registration This study is registered as PROSPERO CRD42022337239, CRD42021229769 and CRD42022374509. The reviews of economic evidence were not registered; however, the review protocol can be accessed via the repository held by Queen's University Belfast Research Portal (https://pure.qub.ac.uk/). Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme (NIHR award ref: NIHR130995) and is published in full in Health and Social Care Delivery Research; Vol. 12, No. 20. See the NIHR Funding and Awards website for further award information. Plain language summary What was the question? We know that breastfeeding is good for the health of mothers and babies, yet many mothers experience difficulties and stop breastfeeding before they want to. This is noticeable among women living in disadvantaged areas where there are low rates of breastfeeding. Good support may help women overcome difficulties so that they can continue to breastfeed. Women with chronic illnesses such as diabetes and depression face additional challenges in breastfeeding. We wanted to understand how to improve breastfeeding support for UK women. What did we do? We brought together previous scientific studies to learn about what works. We also spoke with parents and service providers. We combined all our findings into a toolkit to help the NHS improve breastfeeding support for women. What did we find? We found that, for healthy women, some forms of breastfeeding support can probably help reduce the number of women stopping breastfeeding and help them breastfeed exclusively. For women with chronic illnesses, we found that the types of support used in the studies probably did not help women to breastfeed. Most of the evidence did not come from the UK. We identified barriers to providing breastfeeding support for all women, especially those who are disadvantaged. We identified strategies that could help the NHS overcome these barriers. There was a lack of evidence on how cost-effective these interventions are compared with usual care, but parents and providers saw the value of paying for breastfeeding support. What does this mean? Giving women targeted breastfeeding support will help them to breastfeed; however, we need to test if this support works in the NHS. We also need to develop additional services for women with chronic illnesses. The NHS could use our findings to improve support for all breastfeeding women by identifying specific barriers and using evidence-based strategies to overcome them. Scientific summary Background Breastfeeding impacts positively on multiple health outcomes across the lifespan. Global and UK infant recommendations are that infants should receive breastmilk exclusively for 6 months and as part of a mixed diet until 2 years. However, fewer than half of UK women are breastfeeding at 6-8 weeks, with a marked social gradient. Objectives This study aimed to synthesise global and UK evidence in order to co-create with stakeholders a framework to guide the implementation and evaluation of cost-effective breastfeeding support interventions in the NHS: Update the Cochrane review 'Support for healthy breastfeeding mothers with healthy term babies' (McFadden A, Gavine A, Renfrew MJ, Wade A, Buchanan P, Taylor JL, et al. Support for healthy breastfeeding mothers with healthy term babies. Cochrane Database Syst Rev 2017;2:CD001141). Synthesise process evaluations of breastfeeding support interventions. Conduct an economic evaluation of interventions to enable women to breastfeed. Conduct a systematic review of breastfeeding support interventions for women with long-term conditions (LTCs). Synthesise evidence of barriers to and facilitators of breastfeeding support for women with LTCs. Conduct a systematic review of economic evaluations of breastfeeding support interventions. Co-create a NHS-tailored implementation and evaluation strategy framework to increase breastfeeding rates in the UK. Contribute to methodological development on involving stakeholders in systematic reviews. Design The study comprised two meta-analyses of breastfeeding support interventions, two mixed-methods evidence syntheses and two economic evaluations with embedded stakeholder engagement, including parents' panels, stakeholder working groups, focus groups and workshops.